The beneficial effects of cinnamon among patients with metabolic diseases: A systematic review and dose-response meta-analysis of randomized-controlled trials. Issue 22 (22nd July 2022) - Kutbi, Emad H.; Sohouli, Mohammad Hassan; Fatahi, Somaye; Lari, Abolfazl; Shidfar, Farzad; Aljhdali, Maha Mari; Alhoshan, Faisal Musaad; Elahi, Saad Saif; Almusa, Hashem Ameen; Abu-Zaid, Ahmed
Abstract: This systematic review and meta-analysis aims to summarize and conclude the clinical evidence regarding the use of cinnamon among patients with metabolic diseases. A comprehensive literature search without any limitation on language was conducted using the following bibliographical databases: ISI Web of Science, Embase, Scopus, PubMed, and Google Scholar. Search was conducted up to 23 January 2020. A total of 35 clinical trials were included for final analysis. Pooling of results showed a significant reducing effect of cinnamon on total cholesterol (TC) (weighted mean difference (WMD) = −11.67 mg/dL; P = 0.010), triglyceride (TG) (WMD = −16.27 mg/dL; P < 0.001), low density lipoprotein-cholesterol (LDL-C) (WMD = −6.36 mg/dL; P < 0.001), serum glucose (WMD = −11.39 mg/dL; P < 0.001), serum insulin (WMD = −1.27 μIU/mL; P = 0.028), and waist circumstance (WC) (WMD = −1.68 cm; P = 0.016). These lowering effects on TG, TC, LDL-C, and serum glucose levels were robust in studies that used cinnamon supplementation dose ≤1.5 g. Also, our findings of the present meta-analysis showed that cinnamon supplementation could have favorable effects on high density lipoprotein-cholesterol (HDL-C, WMD = 1.35; P = 0.038) as well as systolic (WMD = −3.95 mmHg; P = 0.018) and diastolic (WMD = −3.36; P = 0.001) blood pressure among patients with metabolic diseases. The present meta-analysis suggests that cinnamon might exert beneficial effects on various cardiometabolic risk factors among patients with metabolic diseases.